(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This article provides an overview of the physical layer of 6G. It highlights the importance of physical layer innovations in the development of 6G networks, suggesting that these innovations are instrumental in shaping the future of wireless communication. In 2018, the completion of 5G marked a significant milestone in wireless communication. It harnessed the potential of the mmWave frequency spectrum and the multiple OFDM (Orthogonal Frequency Division Multiplexing) technique, setting the stage for faster and more reliable connections. However, the physical layer, which forms the backbone of these networks, presents an opportunity for further exploration and innovation. In light of this, researchers have been actively investigating various potential technologies for the physical layer to propel us ’beyond 5G.’ These explorations encompass a range of physical layer advancements, including non-orthogonal multiple access, cost-effective massive MIMO (Multiple-Input Multiple-Output), intelligent antenna systems, terahertz wireless communication, optical wireless communication, and index modulation.